(untitled) (International Journal of Food and Nutritional Sciences, 2022)
GST is an indirect tax paid by customers all over India. It was implemented by the Government of India on 1st July 2017. GST is a single taxation system which is levied on all goods and services. GST will help the economy grow in many ways but also has some positive and negative barriers. The GST rates levied are of four different rates such as 0%, 5%, 12% and 18%. After the implementation of GST, the rates of a few products and services have increased and in the same manner, the rates of a few products and services are decreased. The taxes collected by the Government are of three forms CGST, SGST, and IGST. The rates levied on GST are acceptable by the people for a few products but they feel it is too high for some products. This paper focuses on the perception of GST by the customers and its impact in Thoothukudi district. It also helps to analyze whether the concept of GST is understood by every citizen of the country in Thoothukudi District